Role of Myokines in Regulating Skeletal Muscle Mass and Function - Lee, Jong Han; Jun, Hee-Sook (Frontiers in Physiology, 2019)
Loss of skeletal muscle mass and strength has recently become a hot research topic with the extension of life span and an increasingly sedentary lifestyle in modern society. Maintenance of skeletal muscle mass is considered an essential determinant of muscle strength and function. Myokines are cytokines synthesized and released by myocytes during muscular contractions. They are implicated in autocrine regulation of metabolism in the muscle as well as in the paracrine/endocrine regulation of other tissues and organs including adipose tissue, the liver, and the brain through their receptors. Till date, secretome analysis of human myocyte culture medium has revealed over 600 myokines. In this review article, we summarize our current knowledge of major identified and characterized myokines focusing on their biological activity and function, particularly in muscle mass and function.